Strategi Dakwah Tokoh Masyarakat Dalam Meningkatkan Minat Warga Mengikuti Tahlilan Di Desa Muara Telang Kecamatan Sumber Marga Telang Kabupaten Banyuasin - Edi Karya; Nurseri Hasnah Nasution; Anang Walian (Social Science and Contemporary Issues Journal, 2023)
This research is entitled "Dakwah Strategy of Community Leaders in Increasing Residents' Interest in Participating in Tahlilan in Muara Telang Village, Sumber Marga Telang District, Babyuasin Regency". The purpose of this study was to find out the interest of the people of Muara Telang Village in participating in Tahlilan. to find out the objective conditions of community leaders in the village of Muara Telang. to find out the strategy of community leaders in increasing the interest of residents to take part in Tahlilan in the village of Muara Telang. This type of research is field research and a qualitative approach. This study uses primary data sources and secondary data sources, while data analysis in this study uses observation, interviews, and documentation. The data analysis technique in this study is qualitative descriptive, by means of data reduction, data presentation, and drawing conclusions. The theory used is the da'wah strategy according to Asamuni Syukir. The results of the research are based on interviews conducted in the field. Residents' interest in participating in tahlilan is very low, due to their busy work as farmers, fishermen and gardeners. It is because of these non-sedentary jobs that the community's interest is low. It is hoped that the objective conditions of community leaders can provide enlightenment for the residents in Muara Telang village so that the residents can later become citizens who are obedient and obedient in religion and diligent in following tahlilan. Whereas the strategy used by community leaders in increasing interest in tahlilan is divided into 3, namely the strategy of socializing in the village of Muara Telang, the strategy of inviting ustadz from outside to add new knowledge and insights, the strategy of providing the facilities needed at the tahlilan event, but the problems that exist in the village of Muara Telang this is the first because of the busyness of the people in their activities, they lack religious knowledge and there are still many who do not understand family life.